A view from the UK: the UK and Ireland confidential enquiry into maternal deaths and morbidity - Knight, M; Tuffnell, D (Lippincott, Williams & Wilkins, 2018)
The UK Confidential Enquiry into Maternal Deaths has been in operation for more than 60 years, during which time maternal mortality rates have fallen tenfold. The program includes two aspects, surveillance and confidential case review, providing different information to aid quality improvement in maternity care. The enquiry now also reviews the care of women with specific severe morbidities. Recommendations have very clearly led to improved outcomes for women, most notably shown in the very low mortality rate due to hypertensive and related disorders of pregnancy. Maternal cardiac disease and mental health problems remain the major areas still to be addressed.